Pengembangan LKPD Berbasis STEM (Science, Technology, Engineering, Mathematics) pada Materi Termodinamika - Dea Oktaviany; Nanda Novita; Desy Sary Ayunda; Muliani Muliani; Deasy Siska (Journal on Education, 2024)
This research aims to determine the feasibility and practicality of STEM-based LKPD learning media products on thermodynamics material as a medium that makes it easier for students to study thermodynamics material. The instrument used in the research is a feasibility and practicality questionnaire which will be given by material and media experts and given to teachers in the field of physics and students in class XI IPA 2 MAS Syamsuddhuha. This development research method refers to Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The research results showed that experts in the media field gave a feasibility assessment of 92.3% with a very feasible category, experts in the material field gave an assessment of 88.6% with a feasible category and teacher responses gave an assessment of 86% with a very practical percentage. The results of small-scale product trials gave an assessment of 86.9% in the very practical category and the results of large-scale product trials gave an assessment of 84% in the very practical category.